Ocular Features and Visual Outcome in Patients of Accidental Methanol Poisoning at a Tertiary Care Centre in Eastern India: A Case Series: Ocular features and visual outcome in patients of accidental methanol poisoning in eastern India - Priyadarshini, Surabhi; Kumar, Sunil; Singh, Bhoopendra (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: This study evaluated ocular features and visual outcomes in patients of accidental methanol poisoning at a tertiary centre in Jharkhand, India. Methods: Seven consecutive patients were attended from January 2022 to December 2022 as bedside references in the emergency department of our hospital after accidental ingestion of methanol in the form of adulterated alcoholic beverages. Visual acuity, anterior segment, fundus, and intraocular pressure (IOP) were examined, followed by a magnetic resonance imaging (MRI) of the brain. They were started with intravenous methylprednisolone followed by oral prednisolone. All the patients were followed up for the next three months. Results: The mean age of patients was 36.21±3.3 years (ranging from 29 to 43 years), and all were males. Visual acuity ranged from perception of light to counting fingers at 1 meter. Visual loss was bilateral. The pupillary reaction was sluggish or non-reactive. Fundus pictures ranged from normal to optic disc oedema and tortuous vessels. MRI showed central nervous system involvement in all patients. In follow-up visits, three patients showed normal fundus as in the previous examination, while four patients showed optic atrophy, and none presented with any improvement in visual acuity. Conclusion: It was concluded that methanol causes irreversible visual loss.